Synthesis and Infrared studies on N-(Cyclohexyl)-2-Mercaptoacetamides. - BHAGCHANDANI, PUSHPA; GARG., SHIMLA (Asian Journal of Chemistry, 2010)
The work describes the IR studies of N-(cyclohexyl)-2-mercaptoacetamides.